When is the turning point/climax in the book "Zinnia and the Bees?"
23 answers
The turning point/climax in the book "Zinnia and the Bees" happens when Zinnia realizes that she needs to let the bees go and allow them to live their own lives. She comes to this realization after a conversation with her former friend, Birch, who helps her understand that she cannot keep the bees and control their lives. This realization is a turning point for Zinnia as she learns the importance of respecting other creatures and allowing them to live their own lives.
4. What are the coefficients in the polynomial 5x² + 2x-4? (1 point)
O 5, 2
O -5, -2
O 5, 2, -4
O 5, -2, -4
?
O 5, 2
O -5, -2
O 5, 2, -4
O 5, -2, -4
?
The coefficients in the polynomial 5x² + 2x - 4 are 5, 2, and -4.
Therefore, the answer is: 5, 2, -4.
Therefore, the answer is: 5, 2, -4.
Add or subtract.
5. (m²-m-4)+(m-5) (1 point)
1 m² - 2m + 9
2 m² + 2m - 9
3 m² - 2m - 9
4 m² - 9
?
5. (m²-m-4)+(m-5) (1 point)
1 m² - 2m + 9
2 m² + 2m - 9
3 m² - 2m - 9
4 m² - 9
?
To add (m² - m - 4) and (m - 5), we combine like terms and simplify:
(m² - m - 4) + (m - 5)
= m² - m + m - 4 - 5
= m² - 9
Therefore, the answer is: 4. m² - 9.
(m² - m - 4) + (m - 5)
= m² - m + m - 4 - 5
= m² - 9
Therefore, the answer is: 4. m² - 9.
Add or subtract.
6. (7x^2-x-2)-(-6x^3 + 3) (1 point)
A 6x^3+7x2-x-5
B -6x^3+7x2-x+1
C -x^3-x-5
D x²-x+1
?
6. (7x^2-x-2)-(-6x^3 + 3) (1 point)
A 6x^3+7x2-x-5
B -6x^3+7x2-x+1
C -x^3-x-5
D x²-x+1
?
To subtract (-6x³ + 3) from (7x² - x - 2), we must first distribute the negative sign to all terms inside the parentheses:
(7x² - x - 2) - (-6x³ + 3)
= 7x² - x - 2 + 6x³ - 3
We can simplify the answer by combining like terms:
= 6x³ + 7x² - x - 5
Therefore, the answer is: A) 6x³ + 7x² - x - 5.
(7x² - x - 2) - (-6x³ + 3)
= 7x² - x - 2 + 6x³ - 3
We can simplify the answer by combining like terms:
= 6x³ + 7x² - x - 5
Therefore, the answer is: A) 6x³ + 7x² - x - 5.
8. f^2 . f^4 (1 point)
A (2f)^8
B (2f)^6
C f^8
D f^6
?
A (2f)^8
B (2f)^6
C f^8
D f^6
?
When multiplying exponential expressions with the same base, we must add their exponents.
In this case, we have f^2 and f^4. Adding their exponents, we get:
f² . f⁴ = f^(2+4) = f^6
Therefore, the answer is: D. f^6
In this case, we have f^2 and f^4. Adding their exponents, we get:
f² . f⁴ = f^(2+4) = f^6
Therefore, the answer is: D. f^6
9. 144^14/144^2
(1 point)
A 144^16
B 144^12
C 144^28
D 144^14/2
?
(1 point)
A 144^16
B 144^12
C 144^28
D 144^14/2
?
When dividing exponential expressions with the same base, we must subtract their exponents.
In this case, we have 144^14 in the numerator and 144^2 in the denominator. Subtracting their exponents, we get:
144^(14-2) = 144^12
Therefore, the answer is: B. 144^12.
In this case, we have 144^14 in the numerator and 144^2 in the denominator. Subtracting their exponents, we get:
144^(14-2) = 144^12
Therefore, the answer is: B. 144^12.
10. x^11/x^4 (1 point)
A x^7
B x^15
C x^44
D x^11/4
?
A x^7
B x^15
C x^44
D x^11/4
?
When dividing exponential expressions with the same base, we must subtract their exponents.
In this case, we have x^11 in the numerator and x^4 in the denominator. Subtracting their exponents, we get:
x^(11-4) = x^7
Therefore, the answer is: A. x^7.
In this case, we have x^11 in the numerator and x^4 in the denominator. Subtracting their exponents, we get:
x^(11-4) = x^7
Therefore, the answer is: A. x^7.
11. Which of the following expressions is true? (1 point)
A 4^3 . 4^4 = 4^12
B 5^2 . 5^3 > 5^5
C 3^2 . 3^5 = 3^10
D 5^2 . 5^4 < 5^8
?
A 4^3 . 4^4 = 4^12
B 5^2 . 5^3 > 5^5
C 3^2 . 3^5 = 3^10
D 5^2 . 5^4 < 5^8
?
When multiplying exponential expressions with the same base, we must add their exponents.
Option A: 4^3 . 4^4 = 4^7 = 16384
Option B: 5^2 . 5^3 = 5^5 = 3125. Also, 5^5 > 5^5 is not true.
Option C: 3^2 . 3^5 = 3^7 = 2187
Option D: 5^2 . 5^4 = 5^6 = 15625. Also, 5^6 < 5^8 is not true.
So, the only option that is true is A: 4^3 . 4^4 = 4^7 = 16384.
Option A: 4^3 . 4^4 = 4^7 = 16384
Option B: 5^2 . 5^3 = 5^5 = 3125. Also, 5^5 > 5^5 is not true.
Option C: 3^2 . 3^5 = 3^7 = 2187
Option D: 5^2 . 5^4 = 5^6 = 15625. Also, 5^6 < 5^8 is not true.
So, the only option that is true is A: 4^3 . 4^4 = 4^7 = 16384.
12. Which of the following expressions is true? (1 point)
A 2^4 . 2^4 > 2^7
B 3^2 . 3^6 = 3^7
C 4^3 . 4^5 < 4^8
D 5^2 . 5^3 = 5^6
?
A 2^4 . 2^4 > 2^7
B 3^2 . 3^6 = 3^7
C 4^3 . 4^5 < 4^8
D 5^2 . 5^3 = 5^6
?
When multiplying exponential expressions with the same base, we must add their exponents.
Option A: 2^4 . 2^4 = 2^8 = 256. Also, 2^8 is less than 2^7, so A is not true.
Option B: 3^2 . 3^6 = 3^8 = 6561. Also, 3^7 is less than 3^8, so B is not true.
Option C: 4^3 . 4^5 = 4^8 = 65536.
Option D: 5^2 . 5^3 = 5^5 = 3125. Also, 5^6 is greater than 5^5, so D is not true.
So, the only option that is true is C: 4^3 . 4^5 = 4^8 = 65536.
Option A: 2^4 . 2^4 = 2^8 = 256. Also, 2^8 is less than 2^7, so A is not true.
Option B: 3^2 . 3^6 = 3^8 = 6561. Also, 3^7 is less than 3^8, so B is not true.
Option C: 4^3 . 4^5 = 4^8 = 65536.
Option D: 5^2 . 5^3 = 5^5 = 3125. Also, 5^6 is greater than 5^5, so D is not true.
So, the only option that is true is C: 4^3 . 4^5 = 4^8 = 65536.
Write the value of the expression.
13. 3^4/3^4 (1 point)
0 3
0 0
0 1
0 4
14. 2^2/2^5 (1 point)
A 8
B 6
C 1/8
D -8
13. 3^4/3^4 (1 point)
0 3
0 0
0 1
0 4
14. 2^2/2^5 (1 point)
A 8
B 6
C 1/8
D -8
13. When dividing exponential expressions with the same base, we must subtract their exponents.
In this case, we have 3^4 in both the numerator and denominator. Subtracting their exponents, we get:
3^(4-4) = 3^0
Any non-zero number raised to the power of zero is equal to 1.
Therefore, the value of the expression is: 1.
14. When dividing exponential expressions with the same base, we must subtract their exponents.
In this case, we have 2^2 in the numerator and 2^5 in the denominator. Subtracting their exponents, we get:
2^(2-5) = 2^-3
We can simplify the expression further by realizing that 2^-3 is the same as 1/2^3 or 1/8.
Therefore, the value of the expression is: C. 1/8.
In this case, we have 3^4 in both the numerator and denominator. Subtracting their exponents, we get:
3^(4-4) = 3^0
Any non-zero number raised to the power of zero is equal to 1.
Therefore, the value of the expression is: 1.
14. When dividing exponential expressions with the same base, we must subtract their exponents.
In this case, we have 2^2 in the numerator and 2^5 in the denominator. Subtracting their exponents, we get:
2^(2-5) = 2^-3
We can simplify the expression further by realizing that 2^-3 is the same as 1/2^3 or 1/8.
Therefore, the value of the expression is: C. 1/8.
15. (2.3 . 10¹)(7 . 10^6) (1 point)
A 1.61 . 10^7
B 1.61 . 10^8
C 9.3 . 10^6
D 9.3 . 10^7
16. (1.1 . 10^-5)(3 . 10^-2) (1 point)
A 4.1 . 10^-7
B 4.1 . 10^10
C 3.3 . 10^-7
D 3.3 . 10^10
A 1.61 . 10^7
B 1.61 . 10^8
C 9.3 . 10^6
D 9.3 . 10^7
16. (1.1 . 10^-5)(3 . 10^-2) (1 point)
A 4.1 . 10^-7
B 4.1 . 10^10
C 3.3 . 10^-7
D 3.3 . 10^10
15. When multiplying numbers in scientific notation, we can multiply their coefficients and add their exponents.
In this case, we have (2.3 x 10^1)(7 x 10^6). Multiplying their coefficients, we get:
(2.3)(7) = 16.1
Adding their exponents, we get:
10^1 + 10^6 = 10^7
Therefore, the answer is: A. 1.61 x 10^7.
16. When multiplying numbers in scientific notation, we can multiply their coefficients and add their exponents.
In this case, we have (1.1 x 10^-5)(3 x 10^-2). Multiplying their coefficients, we get:
(1.1)(3) = 3.3
Adding their exponents, we get:
10^-5 + 10^-2 = 10^-7
Therefore, the answer is: C. 3.3 x 10^-7.
In this case, we have (2.3 x 10^1)(7 x 10^6). Multiplying their coefficients, we get:
(2.3)(7) = 16.1
Adding their exponents, we get:
10^1 + 10^6 = 10^7
Therefore, the answer is: A. 1.61 x 10^7.
16. When multiplying numbers in scientific notation, we can multiply their coefficients and add their exponents.
In this case, we have (1.1 x 10^-5)(3 x 10^-2). Multiplying their coefficients, we get:
(1.1)(3) = 3.3
Adding their exponents, we get:
10^-5 + 10^-2 = 10^-7
Therefore, the answer is: C. 3.3 x 10^-7.
Simplify the expression.
17. 6t^3 . 6t^3 (1 point)
A 12t^3
B 12t^6
C 36t^6
D 36t^9
Simplify the expression.
18. -x(5x-4) (1 point)
A 4x² - 5x
B -5x - 4x
C 5x + 4x
D -5x² + 4x
Simplify the expression.
19. 4k²(-3k² - 4k+5) (1 point)
A -12k^4 - 16k^3 + 20k^2
B 12k^4 - 16k^3 + 9k²
C -12k^3 + 20k
D k^4 + 9k^2
Simplify the expression.
20. (2k+1) (k-4) (1 point)
A 2k² - 7k+4
B 2k² -3k + 4
C 2k² + 9k+4
D 2k^2 - 7k - 4
Simplify the expression.
21. (-2y+5)(y+3) (1 point)
A -2y² + 8y + 15
B -2y^2 - y + 15
C 2y² + 8y +8
D 2y^2 - y + 8
17. 6t^3 . 6t^3 (1 point)
A 12t^3
B 12t^6
C 36t^6
D 36t^9
Simplify the expression.
18. -x(5x-4) (1 point)
A 4x² - 5x
B -5x - 4x
C 5x + 4x
D -5x² + 4x
Simplify the expression.
19. 4k²(-3k² - 4k+5) (1 point)
A -12k^4 - 16k^3 + 20k^2
B 12k^4 - 16k^3 + 9k²
C -12k^3 + 20k
D k^4 + 9k^2
Simplify the expression.
20. (2k+1) (k-4) (1 point)
A 2k² - 7k+4
B 2k² -3k + 4
C 2k² + 9k+4
D 2k^2 - 7k - 4
Simplify the expression.
21. (-2y+5)(y+3) (1 point)
A -2y² + 8y + 15
B -2y^2 - y + 15
C 2y² + 8y +8
D 2y^2 - y + 8
17. When multiplying exponential expressions with the same base, we must add their exponents.
In this case, we have 6t^3 in both factors. Adding their exponents, we get:
(6t^3) . (6t^3) = 36t^(3+3) = 36t^6
Therefore, the answer is: C. 36t^6.
18. Distributing the -x to the terms inside the parentheses, we get:
-x(5x - 4) = -5x² + 4x
Therefore, the answer is: D. -5x² + 4x.
19. Distributing the 4k^2 to the terms inside the parentheses, we get:
4k²(-3k² - 4k + 5) = -12k^4 - 16k^3 + 20k²
Therefore, the answer is: A. -12k^4 - 16k^3 + 20k².
20. Using the distributive property, we can multiply each term of the first factor by each term of the second factor:
(2k + 1) (k - 4) = 2k² - 8k + k - 4 = 2k² - 7k - 4
Therefore, the answer is: D. 2k^2 - 7k - 4.
21. Using the distributive property, we can multiply each term of the first factor by each term of the second factor:
(-2y + 5) (y + 3) = -2y² - 6y + 5y + 15 = -2y² - y + 15
Therefore, the answer is: B. -2y^2 - y + 15.
In this case, we have 6t^3 in both factors. Adding their exponents, we get:
(6t^3) . (6t^3) = 36t^(3+3) = 36t^6
Therefore, the answer is: C. 36t^6.
18. Distributing the -x to the terms inside the parentheses, we get:
-x(5x - 4) = -5x² + 4x
Therefore, the answer is: D. -5x² + 4x.
19. Distributing the 4k^2 to the terms inside the parentheses, we get:
4k²(-3k² - 4k + 5) = -12k^4 - 16k^3 + 20k²
Therefore, the answer is: A. -12k^4 - 16k^3 + 20k².
20. Using the distributive property, we can multiply each term of the first factor by each term of the second factor:
(2k + 1) (k - 4) = 2k² - 8k + k - 4 = 2k² - 7k - 4
Therefore, the answer is: D. 2k^2 - 7k - 4.
21. Using the distributive property, we can multiply each term of the first factor by each term of the second factor:
(-2y + 5) (y + 3) = -2y² - 6y + 5y + 15 = -2y² - y + 15
Therefore, the answer is: B. -2y^2 - y + 15.